E-learning tool and statistical analysis of video tace files over the network - Gohar Sargsyan (Изд-во НАН РА)
The following paper offers an overview on the e-learning tool “Dileco” system structure and the advancement of features of it. The main features of this tool aim to support operations, using unstable and limited Internet connection, utilizing novel solutions outlined in this paper. This system would be one of the best tools applicable for e-learning in countries with poor Internet. The paper pursues the objectives of showing some of the innovative features of the system and demonstrates the progress of the system starting from 2002. This paper aims to express technological aspects on building this system. It offers a snapshot of application areas of the system and provides suggestions for future expansion of application areas, and content creation, particularly, on topics of statistics and mathematics. It is provided with statistical analysis of H.263 video traces over the network.
Keywords: Mathematics